1977
DOI: 10.1080/15287397709529486
|View full text |Cite
|
Sign up to set email alerts
|

Covalent binding and endogenous incorporation as illustrated by nitroso carcinogens

Abstract: Serious problems of interpretation may arise when metabolic studies are carried out with radioactively labeled drugs and other foreign chemicals. Detection of free or bound radioactivity in tissues or body fluids may indicate the presence of the unchanged chemical or of various products of its decomposition. Some radioactivity may, however, represent incorporation of certain metabolites of foreign chemicals into body constituents by normal biosynthetic pathways. The interpretation of the results of such metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1977
1977
1994
1994

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The methyl group which is split off will however, also react with water to form methanol and formaldehyde (Magee 1977). These are either oxidized to carbon dioxide which is exhaled or are incorporated via normal metabolic pathways in the one-carbon pool of the body (Magee 1977). Therefore, if a cleavage of the labelled methyl group of the N-nitrosomethylurea side-chain of streptozotocin occurs, 14COo exhalation and incorporation of radioactivity in the macromolecules of the tissues may be expected.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…The methyl group which is split off will however, also react with water to form methanol and formaldehyde (Magee 1977). These are either oxidized to carbon dioxide which is exhaled or are incorporated via normal metabolic pathways in the one-carbon pool of the body (Magee 1977). Therefore, if a cleavage of the labelled methyl group of the N-nitrosomethylurea side-chain of streptozotocin occurs, 14COo exhalation and incorporation of radioactivity in the macromolecules of the tissues may be expected.…”
mentioning
confidence: 96%
“…N-nitrosomethylurea, which constitutes the side-chain of strepto¬ zotocin (Herr et al 1967), has been shown to methylate nucleic acids in several organs of rats (Swann 8c Magee 1968). The methyl group which is split off will however, also react with water to form methanol and formaldehyde (Magee 1977). These are either oxidized to carbon dioxide which is exhaled or are incorporated via normal metabolic pathways in the one-carbon pool of the body (Magee 1977).…”
mentioning
confidence: 99%
“…The studies presented at this symposium by Magee (1977) illustrate that dimethylnitrosamine, a carcinogen present in many foods, is converted to formaldehyde that serves as a precursor of the methyl group of methionine. Moreover, studies by Rosenblum (p. 803) illustrated that at least a portion of some foreign compounds may ultimately be converted into threonine, an essential amino acid in rats.…”
Section: Kinetics Of Radioisotopes In Labeled Drugsmentioning
confidence: 97%